The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18608/jla.2021.7242
|View full text |Cite
|
Sign up to set email alerts
|

Designing Analytics for Collaboration Literacy and Student Empowerment

Abstract: Collaboration has garnered global attention as an important skill for the 21st century. While researchers have been doing work on collaboration for nearly a century, many of the questions that the field is investigating overlook the need for students to learn how to read and respond to different collaborative settings. Existing research focuses on chronicling the various factors that predict the effectiveness of a collaborative experience, or on changing user behaviour in the moment. These are worthwhile resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In the second article, Worsley, Anderson, Melo, and Jang (2021) talk about the importance of developing new data collection tools for supporting collaboration analytics. They present a paper describing the development of a tool called BLINC (Building Literacy in In-Person Collaboration) that was informed by data collected from university students regarding their concerns about collaboration.…”
Section: Summary Of Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second article, Worsley, Anderson, Melo, and Jang (2021) talk about the importance of developing new data collection tools for supporting collaboration analytics. They present a paper describing the development of a tool called BLINC (Building Literacy in In-Person Collaboration) that was informed by data collected from university students regarding their concerns about collaboration.…”
Section: Summary Of Papersmentioning
confidence: 99%
“…Collaboration analytics is a perfect example of this -by developing new data collection tools that allow us to visualize social interactions in real time, it could allow students to better understand group interactions and how to interact with others. The BLINC platform (Worsley et al, 2021) is a first step in this direction. By providing information about the group's discussion, the tool allows students to start a conversation on how their collaborative processes could be improved.…”
Section: What Is Collaboration Analytics?mentioning
confidence: 99%
“…Further, we incorporate the use of ENA and its visualisations to support our collaborative autoethnography process. This use of ENA primarily to support our reflective process (Alhadad, 2018;Worsley et al, 2021) (rather than of analysis of research findings per se) is novel. Collectively, all authors found that our collaborative reflections were enhanced using ENA as it helped us interrogate and question our assumptions and understanding of each other, and in supporting our reflexivity beyond what we were able to engage in prior to introducing the ENA in our CAE.…”
Section: Concluding Reflections and Implicationsmentioning
confidence: 99%
“…Additionally, current research showcases an urgency for guiding systems: Molenaar and Knoop-Van Campen (2019) and Amarasinghe et al (2020) suggest that a recommendation service should be developed to existing LA systems. Correspondingly, Worsley et al (2021) specifically draw attention to the need for systems identifying problems and at the same time offering possible avenues for solving the issues. Ultimately, the focus of collaboration analytics should be on really having an impact on teaching and learning about how to collaborate better (Wise and Jung, 2019;Worsley et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, Worsley et al (2021) specifically draw attention to the need for systems identifying problems and at the same time offering possible avenues for solving the issues. Ultimately, the focus of collaboration analytics should be on really having an impact on teaching and learning about how to collaborate better (Wise and Jung, 2019;Worsley et al, 2021). Until now, what kind of pedagogical action to choose for a particular group of students has remained an untouched avenue (van Leeuwen and Rummel, 2020).…”
Section: Introductionmentioning
confidence: 99%